Catherine of Siena on persons created in God"s image: Basis for a spiritual path - Villegas, Diana L. (HTS teologiese studies, 2024)
The belief that persons are images of God offers powerful constructs for imagining and thinking about a spiritual journey. What about; who we are makes a relationship possible with God? What are the goals of a spiritual journey given who we are to God? Catherine of Siena’s wisdom regarding persons as images of God offers answers to these questions. This study presents a textual analysis of Catherine’s metaphor-filled rhetoric on this topic and shows how Catherine, an uneducated woman mystic appropriated the foundational systematic teaching of Augustine of Hippo on persons as images of God having memory, understanding and will. Catherine asserts that persons as images of God having these three powers of the soul are created out of God’s love with a capacity to love and to be in a relationship of love, first of all, with God. The spiritual journey essentially consists in transcending – through God’s redemptive love – all that obscures this created capacity.Contribution: This study contributes by highlighting the importance of theological anthropology – both as a theological tenet and as a belief – to the way persons imagine and live a spiritual journey. Furthermore, it shows how Augustine of Hippo’s formulations, foundational for Christianity, influenced a medieval mystic and can be relevant for spiritual practice today. Accordingly, this study concludes with suggestions about how this patristic and medieval understanding of persons can be appropriated for today’s spiritual life.